Inventory management systems of small and medium enterprises in Bangladesh - Md. Kausar Alam; Oli Ahad Thakur; Fakir Tajul Islam (Rajagiri Management Journal (RAMJ), 2024)
Purpose - Inventory is a crucial part of a systematic supply chain of a business. Small firms mostly neglect inventory management (IM) by accumulating excessive inventory for a time. The study aims to examine the IM practices of small and medium enterprises (SMEs) in Bangladesh. Design/methodology/approach - The study applied a qualitative case study design. Data were collected from ten SME owners in Bangladesh. The study employed a purposive sampling technique to collect data. This study used semi-structured interviews to generate data. The NVivo software was used to analyze the data. Findings - The findings show that most SME business owners collect raw materials from the local market. Along with the local sources, they collect raw materials from international markets. Some SME entrepreneurs collect raw materials throughout the country as they dealt with recycled products. Frequently, they used digital technologies and online media to manage raw materials. SME owners could not buy many raw materials due to financial crisis, wastage, and damage, leading to a ratio of 10-15% losses. Research limitations/implications - This research contributes greatly to the government, SME Foundation, and trade associations concerning the SME IM system. The study recommends the government should reduce the tax rate on importing SME raw materials and inventories and exporting SME products. Originality/value - This is the first study that focuses on the IM systems of SMEs in Bangladesh.
Keywords: 650; Inventory management; SME; SME owners; Qualitative research; Bangladesh